2022
DOI: 10.1080/00365521.2021.2023626
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of nomogram based on Kyoto classification of gastritis to diagnosis of gastric cancer

Abstract: Background and Aim. It is of importance to predict the risk of gastric cancer (GC) for endoscopists because early detection of GC determines the determines the selection of best treatment strategy and the prognosis of patients. The aim of the study was to evaluate the utility of a predictive nomogram based on Kyoto classi cation of gastritis for GC.Methods. It was a retrospective study that included 2639 patients who received esophagogastroduodenoscopy and serum pepsinogen (PG) assay from January 2020 to Novem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, as we want more precise data to predict, it is essential to check the Kyoto Classification score’s accuracy with further high-quality research. [34] A more accurate Kyoto Classification score should be determined via more studies in order to practice precision medicine. Additional assessment markers, such as white sticky mucus and spotty redness, should be included in the Kyoto Classification of Gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as we want more precise data to predict, it is essential to check the Kyoto Classification score’s accuracy with further high-quality research. [34] A more accurate Kyoto Classification score should be determined via more studies in order to practice precision medicine. Additional assessment markers, such as white sticky mucus and spotty redness, should be included in the Kyoto Classification of Gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…The total Kyoto scores of patients with GC, H. pylori -infected GC, and H. pylori -eradicated GC were 4.0-4.6, 4.8-5.6, and 4.2, respectively[ 44 , 50 , 58 , 60 ]. A high total Kyoto score was associated not only with GC (ORs = 1.5-1.6), but also with both diffuse-type and intestinal-type GCs (ORs = 1.3 and 1.7, respectively, Table 4 )[ 44 , 61 ]. Additionally, some investigators showed that the incidence of GC increased stepwise with the total Kyoto scores of 0-1, 2-3, ≥ 4, and that the AUC of the nomogram to predict GC using the total Kyoto score was 0.79[ 31 , 61 ].…”
Section: Gc Risk Of Kyoto Classificationmentioning
confidence: 99%
“…A high total Kyoto score was associated not only with GC (ORs = 1.5-1.6), but also with both diffuse-type and intestinal-type GCs (ORs = 1.3 and 1.7, respectively, Table 4 )[ 44 , 61 ]. Additionally, some investigators showed that the incidence of GC increased stepwise with the total Kyoto scores of 0-1, 2-3, ≥ 4, and that the AUC of the nomogram to predict GC using the total Kyoto score was 0.79[ 31 , 61 ]. Taken together, a total Kyoto score of 4 or more is useful for determining GC risks, including histological subtypes, even after H. pylori eradication.…”
Section: Gc Risk Of Kyoto Classificationmentioning
confidence: 99%
“…The interobserver agreement for endoscopic atrophy diagnosis and grading was reported to improve after training and remain stable [16]. Additionally, the incidence of GC increased gradually with EKC scores of 0–1, 2–3, and 4 [8, 17, 18]. As gastric atrophy is a component of EKC and the classification EKC also integrates other components related to the risk of GC, such as diffuse redness, which is associated with active inflammation, and IM, it is presumed that EKC can predict GC risk better than KTC, which is based on gastric atrophy assessment alone.…”
Section: Introductionmentioning
confidence: 99%